HUBUNGAN ANTARA UMUR, NUTRISI DAN INDEKS MASA TUBUH TERHADAP PENYEMBUHAN LUKA POST SC PADA IBU NIFAS - Dian Nirmala Sari; Umi Nur Fajri (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2020)
In Indonesia, the incidence of caesarean section increased by 9.8 percent from a total of 49,603 births from 2010 to 2013. Sections of caesarea are the primary choice for medical personnel to save mothers and fetuses. Post operative wound infection is one of the main problems in surgical practice. The purpose of this study was to determine the relationship between age, nutrition and body mass index on post-SC wound healing in postpartum mothers. Quantitative research methods with a cross sectional approach. The sample in this study were all post SC postpartum mothers at Hj.Anna Lasmanah Banjarnegara Hospital. The results of age study were not related to post SC wound healing p value 0.369. Nutrition is related to post SC wound healing value of p value 0.001. The mother's body mass index is not related to post-SC wound healing value of p value 0.354. Suggestions for health workers Hj. Anna Lasmanah, the executor in the puerperium service room, collaborated with the nutrition department to provide nutrients that contain lots of protein